Resilience to crisis. Determinants of Romanian Economy Resilience - Sorin SOMITCA; Alina SOMITCA; Elena HLACIUC (Communications of International Proceedings, 2022)
Financial crisis, severe recessions, economic shocks are frequent on the one hand as an evolution of natural economic cycles (economic downturn, industry shocks, currency crises) or appearing as a result of disruption of external factors such as the COVID health crisis, rising energy and gas prices globally this year or the current conflict between Russia and Ukraine which creates uncertainty in terms of economic stability or the consequences of sanctions imposed by EU and the US with an unquantified impact on the global economy. Their effect on the economy is persistent and often exceeds initial projections but each economy has its specificity to react to crises and recessions proving a certain level of resilience that can be strengthened. The dilemma of all researcher and economists is why a country is more vulnerable to economic shock than other and which the determinant factors for a strong resilience are as there are no universally agreed definition for resilience. The purpose of the present research is to try to respond these questions by analyzing the impact on economic growth of 8 indicators, namely Resource Productivity, Energy Dependency, Nominal Labour Productivity, Labour Transition, Integration of Internal Process, Circular Material Use, Exports of Goods and Services, R&D Expenditure, analyzing the case of Romania.
Keywords: Resilience; Economic Growth; Turbulence; Economic Crisis